Comparing rhythm in speech and music: The case of English and Polish - Jekiel, Mateusz (Yearbook of the Poznan Linguistic Meeting, 2014)
The point of departure for the following study is Patel and Daniele (2003), who suggested that the rhythm of a culture’s language is reflected in its instrumental music. The former study used the normalised pairwise variability index (henceforth nPVI), a measure of temporal patterning in speech, to compare the variability of vocalic duration in recorded speech samples with the variability of note duration in music notation on the example of English and French speech and classical music. The aim of this experiment is to test whether the linguistic rhythm conventionalised in the language of a community affects the rhythm in the musical practice of that community, by focusing on English and Polish speech and classical, as well as folk music. The nPVI values were obtained from a set of English and Polish recorded news-like sentences, and from musical notation of English and Polish classical and folk musical themes. The results suggest that reflections of Polish speech rhythm may be more apparent in folk music than in classical music, though more data are needed to test this idea. This initial study suggests that the method used might bring more fruitful results when comparing speech rhythm with less formalized and more traditional musical themes.